2022
DOI: 10.3389/fmolb.2022.982276
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the misfolding and self-assembly mechanism of TTR (105–115) peptides by all-atom molecular dynamics simulation

Abstract: Pathological aggregation of essentially dissociative Transthyretin (TTR) monomers protein, driven by misfolded and self-interaction, is connected with Amyloid Transthyretin amyloidosis (ATTR) disease. The TTR monomers protein contains several fragments that tend to self-aggregate, such as residue 105–115 sequence [TTR (105–115)]. However, the misfolding and aggregation mechanisms of TTR are still unknown. In this study, we explored the misfolding and self-assembly of TTR (105–115) peptides by all-atom molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Representative ATTR (105–115) conformations of the bilayer β-sheet and β-barrel from the cluster analysis of MD simulations for the 4-, 6-, and 8-peptide systems (Supporting Figures S4–S6, respectively) indicate that the overall probability of β-barrels (31.28%) is greater compared to bilayer β-sheets (17.83%). It has been reported that four and six peptides of ATTR (105–115) form β-barrel intermediates and subsequently aggregate into fibers …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Representative ATTR (105–115) conformations of the bilayer β-sheet and β-barrel from the cluster analysis of MD simulations for the 4-, 6-, and 8-peptide systems (Supporting Figures S4–S6, respectively) indicate that the overall probability of β-barrels (31.28%) is greater compared to bilayer β-sheets (17.83%). It has been reported that four and six peptides of ATTR (105–115) form β-barrel intermediates and subsequently aggregate into fibers …”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that four and six peptides of ATTR (105−115) form β-barrel intermediates and subsequently aggregate into fibers. 30 Over time, snapshots of the 4-and 6-peptide bilayer and 8peptide monolayer at 100 ns intervals are presented in Figures S11, S12, and S13, respectively. It is evident that the 4-peptide bilayer is dominated by β-sheet conformations.…”
Section: Conformation Of β-Sheet Oligomers Corresponding To the Numbe...mentioning
confidence: 99%
“…The first reason comes from the high propensity of β-sheets revealed by oligomer simulations at a very high concentration of small fragments of Aβ (Aβ16-22, Aβ37-42, Aβ25-35, Aβ10-24 and Aβ35-40), tau (PHF6 motif, repeats R1-R4), transthyretin (105-115) and β2-microglobulin (83-89) peptides which also form fibrils. [29][30][31][32][33][34][35][36] It is notable, however, that two simulations on Aβ16-22 oligomers proposed helical intermediates. [37][38][39] Second, the preference for β-sheet formation comes from the fact that many computational methods do not explore the full conformational ensemble.…”
Section: Random Coil Oligomers With β-Sheet Contentmentioning
confidence: 99%